Long-Term Clinical Outcomes and Parental Satisfaction After Dextranomer/Hyaluronic Acid (Dx/HA) Injection for Primary Vesicoureteral Reflux - Lightfoot, Michelle; Bilgutay, Aylin N.; Tollin, Noah; Eisenberg, Scott; Weiser, Jake; Bryan, Leah; Smith, Edwin; Elmore, James; Scherz, Hal; Kirsch, Andrew J. (Frontiers in Pediatrics, 2019)
Purpose: Endoscopic dextranomer/hyaluronic acid (Dx/HA) injection is a common treatment for vesicoureteral reflux (VUR) with excellent reported short-term clinical success rates. Long-term outcomes are less well-defined. We assessed long-term outcomes and parental satisfaction after Dx/HA injection for primary VUR with >5-year follow-up. Materials and Methods: Families of all patients who underwent Dx/HA injection for primary VUR at our institution between 2008 and 2012 were contacted for telephone interview. Data collected by phone included parental satisfaction and presence and severity of UTIs pre-operatively and post-operatively. Patient demographics, radiographic VUR data, need for secondary surgery, and surgical indications were obtained through chart review. Results: Five hundred and seventy-five patients underwent Dx/HA injection for primary VUR between 2008 and 2012. Ninety-nine (17.2%) of these patients' parents were successfully contacted and interviewed. Median follow-up time from surgery to survey was 8.4 (IQR 6.8–9.6) years. Secondary surgery was performed in 13/99 (13.1%), most commonly repeat Dx/HA injection. Seven patients (7.1%) underwent secondary Dx/HA injection for persistent VUR without UTIs at a median of 0.35 (IQR 0.33–0.77) years post-operatively. Five patients (5.1%) underwent Dx/HA injection (n = 3) or ureteral reimplantation (n = 2) for VUR with febrile UTIs (fUTIs) at a median of 2.2 (IQR 1.3–5.1) years. One patient had ureteral reimplantation for symptomatic obstruction 2.8 years after initial surgery. Only 3/99 (3.0%) required open or laparoscopic surgery after Dx/HA injection. Eighty-three families (84.7%) reported ≥1 fUTIs pre-operatively. Of these, only 9/83 (10.8%) reported fUTIs post-operatively, for an overall clinical success rate of 89.2%. Clinical success was 93.1% in patients whose pre-operative fUTIs were treated outpatient and 80.0% in those hospitalized at least once for fUTI treatment pre-operatively. Ninety-four percent of parents were highly satisfied, 2.4% partially satisfied, and 3.5% dissatisfied. Conclusions: Endoscopic injection with Dx/HA for primary VUR appears to have good long-term clinical success rates and high parental satisfaction, mirroring our previously reported short-term results. Post-operative ureteral obstruction is rare but may occur years post-operatively, justifying initial sonographic surveillance, and repeat imaging in symptomatic patients.